Development of New Measuring Systems Based on Symmetric Components in Electric Networks - Marković, N.; Jakšić, U.; Bjelić, S.; Vujičić, M. (Elektronika ir Elektrotechnika, 2010)
This paper describes real-time functions of development measuring system in distributive electric network and structure of the system for acquisition in systems for measuring, protection and control. Here are presented particularities of process and projecting of DSP processor in which base is digital filter that acquistions, processes and transfer to SCADA all data of possible failures in the moment of their occurrence and new models that are used in the system analysis (behaviour simulations) for the purpose of adjustment of parameters. It has been shown that the third harmonic is one of the most dominant quantities, which reliably and accurate describes situation in electric network.